2022
DOI: 10.3390/cancers14112789
|View full text |Cite
|
Sign up to set email alerts
|

Proton Therapy in the Management of Pancreatic Cancer

Abstract: Radiation therapy plays a central role in the treatment of pancreatic cancer. While generally shown to be feasible, proton irradiation, particularly when an ablative dose is planned, remains a challenge, especially due to tumor motion and the proximity to organs at risk, like the stomach, duodenum, and bowel. Clinically, standard doses of proton radiation treatment have not been shown to be statistically different from photon radiation treatment in terms of oncologic outcomes and toxicity rates as per non-rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…This variability could potentially lead to unexpected complications such as gastrointestinal ulcers, hemorrhage, and perforation in the worst case. In proton therapy for pancreatic cancer, the gastrointestinal toxicity risk remains high [31] , [32] , prompting various studies aimed to reduce the toxicity risk [33] , [34] . Robustness evaluations for the stomach and duodenum during the treatment plan creation is one approach to mitigate dose uncertainties.…”
Section: Discussionmentioning
confidence: 99%
“…This variability could potentially lead to unexpected complications such as gastrointestinal ulcers, hemorrhage, and perforation in the worst case. In proton therapy for pancreatic cancer, the gastrointestinal toxicity risk remains high [31] , [32] , prompting various studies aimed to reduce the toxicity risk [33] , [34] . Robustness evaluations for the stomach and duodenum during the treatment plan creation is one approach to mitigate dose uncertainties.…”
Section: Discussionmentioning
confidence: 99%
“…No grade ≥3 hypofractionated RT-related toxicities were observed, presenting a similar toxicity profile to that of long-course RT. The strength of our study is that some patients were treated with PBT, which is expected to overcome the limitations of conventional IMRT and to potentiate the accurate delivery of high doses to the target [37] . Kim et al .…”
Section: Discussionmentioning
confidence: 99%
“…In several studies comparing proton and photon plan in pancreatic cancer, the PBT plans showed significant lower doses to normal organs like liver, duodenum, small bowel. Dose reduction to radiosensitive normal organs can translate to a potential decline in both acute and long-term RT related toxicities and consequently fewer interruptions to intensive and aggressive systemic therapy [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. In addition, PBT can reduce radiation induced lymphopenia, known as an unfavourable prognostic factor, by decreasing low dose irradiated volume of normal organs like spine and vessels [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, radiation exposure to surrounding normal organs can be minimised [ 12 ]. Several studies have demonstrated that the radiation exposure of normal organs including liver, duodenum, and small bowel can be reduced using proton beam than photon beam in the treatment planning [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. Based on the advantages of PBT, the application of stereotactic body PBT (SBPT) with chemotherapy is expected to improve LC in the management of pancreatic cancer.…”
Section: Introductionmentioning
confidence: 99%